Compositional Characteristics and Antioxidant Activity of Edible Rose Flowers and Their Effect on Phenolic Urinary Excretion - Andrea Devecchi; Sonia Demasi; Francesca Saba; Rosalba Rosato; Roberto Gambino; Valentina Ponzo; Antonella De Francesco; Paola Massarenti; Simona Bo; Valentina Scariot (Polish Journal of Food and Nutrition Sciences)
Petals of edible flowers (EF) are rich in biologically active compounds with many proven benefits for human health. However, studies on the effects of EF in humans after consumption are lacking. This pilot explorative study evaluated the changes in urinary phenolic excretion in healthy volunteers to whom different doses of phenolics from edible roses (Gourmet Roses™) have been added to a meal. Rose petals were picked fresh once a week for three weeks, showing significantly increasing values of total phenolic content, total anthocyanin content, and antioxidant activity (measured as ferric reducing antioxidant power (FRAP) and as DPPH • and ABTS •+ scavenging activities) from the first to the third week. After the meal, direct associations between urinary phenolics and both the EF phenolic content and the antioxidant activity were found in a multiple regression model. These new insights on EF consumption, to be confirmed by larger trials, suggest that the urinary phenolic excretion of healthy volunteers increases with increasing rose phenolic content.